PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA LQ-45 - Nika Ardila; Nur Aida Arifah Tara; Burhanudin Burhanudin (Master of Management, Mataram University, 2021)
This study aims to examine the effect of investment and funding decisions on firm value with profitability as a mediating variable in companies included in the LQ45 index for the 2015-2019 period. The results on the t test show that the positive investment decision is not significant to profitability. The funding decision is negative and not significant to profitability. Investment decisions are positive and significant to firm value while negative funding decisions are not significant to firm value. Profitability is positive and significant to firm value. The results of the mediation test show that profitability is not able to mediate the effect of investment decisions and funding decisions on firm value.Keywords:Keputusan Investasi, Keputusan Pendanaan, Profitabilitas, Nilai Perusahaan